Structural shifts in China’s oil and gas CH4 emissions with implications for mitigation efforts - Junjun Luo; Helan Wang; Hui Li; Bo Zheng (Nature Communications)
Abstract Methane (CH4) is a potent and short-lived climate pollutant, with the oil and gas sectors emerging as an important contributor. China exhibited a substantial expansion of oil and gas infrastructures over recent years, but the CH4 emission accounting tends to be incomplete and uncertain. Here, we construct a CH4 emission database of China’s oil and gas systems from 1990–2022 with 80% of emissions tracked as refineries, facilities, pipelines, and field sources. Results show that China’s oil and gas CH4 emissions have risen from 0.5[0.5–0.6] TgCH4 yr−1 in 1990 to 4.0[3.7–4.4] TgCH4 yr−1 in 2022, primarily driven by the growing demand for natural gas during the energy transition. The spatial details provided are critical for characterizing emission hotspots, especially in unconventional gas production fields and densely populated eastern regions. This long-time series and spatially explicit CH4 emission database can contribute to informed policy decisions and swift climate action.